(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Mobile is used anywhere in this modern world. Technological advancement has made everything viable with one contact. By the use of the programs installed on the cell phones the users pay any payments and transact their cash with everybody in their comfort. The boom in the use of cellular telephones and the net is the principal cause of mobile pocket penetration. This has a look at changed into done to discover the elements that affect customers’ desire in the direction of the mobile pockets. Using an established questionnaire number one information change into gathered from 600 respondents. Chi-square test, ANOVA, and frequency analysis were used to find out the thing that impacts patron preference and the Impact of demographic factors on purchaser desire toward mobile wallets was also analyzed.